Coupon scale Z-pinned IM7/8552 delamination tests under dynamic loading - Cui, Hao; Mahadik, Yusuf; Hallett, Stephen R.; Partridge, Ivana K.; Allegri, Giuliano; Ponnusami, Sathiskumar A.; Petrinic, Nik (Elsevier, 2019)
Dynamic impact onto laminated composite structures can lead to large-scale delamination. This can be mitigated by the introduction of through-thickness reinforcement, such as z-pins. Here, mode I & II and mixed-mode delamination tests have been designed and conducted at high loading rate, for both unpinned and Z-pinned coupons to study the effect of rate of loading. It was found that the Z-pins were not effective in delaying the dynamic crack initiation or resisting the dynamic propagation of delaminations shorter than 5 mm. However, the further growth of cracks was substantially delayed by Z-pinning, especially for the pure mode I and mode I dominated failure modes. On the other hand, the effectiveness of Z-pins in shear tests was relatively modest. The mode I dominated delamination resistance of Z-pinned laminates was found to be sensitive to the loading rate.
Keywords: Through-thickness reinforcement; Delamination; Fracture Mechanics